Polymer Microcapsules Encapsulating Photocatalyst Nanoparticles for Dye Treatment in Wastewater - Srisawang, Narudee; Ngernchuklin, Piyalak; Chaiyasat, Amorn; Chaiyasat, Preeyaporn (Journal of Applied Research on Science and Technology (JARST), 2020)
In this work, poly(methyl methacrylate-acrylic acid-divinyl benzene) (P(MMA-AA-DVB)) microcapsules encapsulating both bismuth vanadate (BiVO4) and magnetite (Fe3O4) nanoparticles were prepared by microsuspension iodine transfer polymerization for the treatment of dyes in wastewater. The colloidal stable spherical microcapsules with high encapsulation efficiency were produced. The extraction of PMMA segment in polymer microcapsule shell using various solvents was carried out to increase the porosity of polymer shell leading to the increase of dye and encapsulated nanoparticle interaction. It was found that using polymer microcapsules at 0.5 wt% of acetone as a solvent presented the highest dye removal efficiency equal to that of pristine BiVO4 nanoparticles. The dye removal efficacy of the microcapsules was gradually reduced when they were reused for 5 times. However, the treatment efficiency was still higher than 50 %. Therefore, the obtained P(MMA-AA-DVB) microcapsules exhibited high performance for dye treatment in wastewater.